Bile spillage and bacterobilia as risk factors for surgical site infection after laparoscopic cholecystectomy: a prospective study at tertiary care hospital - Porwal, Rekha; Soni, Aakanksha; Singh, Amit; Somani, Shruti K.; Sagar, Poornima (International Surgery Journal, 2019)
Background: Surgical site infection (SSIs), a significant postoperative complication, can lead to considerable patient’s morbidity and mortality. Methods: The study was conducted in the Department of Surgery, J.L.N. Medical College and Hospitals, Ajmer from January 2017 to September 2018. The study population constituted cases of cholelithiasis diagnosed by ultrasonography that underwent laparoscopic cholecystectomy and fulfilling the inclusion and exclusion criteria. Surgical site infection was graded according to Southampton grading system. Results: The overall frequency of SSI infection in laparoscopic cholecystectomy was 6%. The occurrence of surgical site infection in patients with bacterobilia was 14.28% which was found to be statistically significant. The SSIs in patients with gall bladder content spillage was found to be statistically insignificant. Conclusions: The frequency of SSI was more in patients with bacterobilia. The gallbladder content spillage does not lead to an increased occurrence of SSI.